Drivers of survival of translocated tortoises. Issue 2 (18th January 2023) - Mack, Jeremy S.; Berry, Kristin H.
Abstract: Translocation of animals, especially for threatened and endangered species, is a currently popular but very challenging activity. We translocated 158 adult Agassiz's desert tortoises ( Gopherus agassizii ), a threatened species, from the National Training Center, Fort Irwin, in the central Mojave Desert in California, USA, to 4 plots as part of a long‐distance, hard‐release, mitigation‐driven translocation to prevent deaths from planned military maneuvers. We monitored demographic and behavioral variables of tortoises fitted with radio‐transmitters from 2008 to 2018. By the end of the project, 17.72% of tortoises were alive, 65.82% were dead, 15.19% were missing, and 1.27% were removed from the study because they returned to Fort Irwin. Mortality was high during the first 3 years: >50% of the released animals died, primarily from predation. Thereafter, mortality declined but remained high. After 10.5 years, survival was highest, 37.50% (15/40), on the plot closest to original home sites, whereas from 2.56% to 23.68% remained alive on the other 3 release plots. Surviving tortoises settled early, repeatedly using locations where they constructed burrows, compared with tortoises that died or disappeared. Models of behavioral and other variables indicated that numbers of repeatedly used locations (burrows) were a driver of survival throughout the study, although plot location, size and sex of tortoises, and distance traveled were contributors, especially during early years. Because >50% mortality occurred, we considered this translocation unsuccessful. The study area appeared to be an ecological sink with historical and current anthropogenic uses contributing to habitat degradation and a decline in both the resident and released tortoises. Our findings will benefit design and selection of future translocation areas. Abstract : In 2008, we translocated 158 adult desert tortoises from a military base in a long‐distance, mitigation‐driven translocation in the central Mojave Desert of California, USA, into a low density, declining resident population. At the end of the 10.5‐year project, few tortoises remained alive, primarily because of predation. Plot location (closer to home site), size and sex of tortoise (large males), and repeatedly used burrows during temperature extremes contributed to survival.